BEHIND THE CIRCUS HAPPINESS: EXPLOITATION OF LABOR - Annur, Ghinia Yusri; Hasan, Nurrahmawati Setya; Manzyla, Khitta El; Fauza, Annisa Sarah; Mintarsih, Mimin (Fakultas Hukum Universitas Swadaya Gunung Jati, 2025)
Behind the glittering circus performances that invite admiration, and are perceived to be full of happiness and wonder, there is a bitter reality that is rarely revealed: the exploitation of labor. This article uses juridical-normative methods and case study approaches. The purpose of this paper is to examine the compatibility between labor practices in the circus world and the applicable labor law provisions, as well as identify the legal protection that will be provided to workers and examine those who will be responsible for the violation of workers' rights. The results of the study show that behind the stunning performance, there are exploratory work practices in the form of excessive working hours, disproportionate wages, unsafe working conditions, and violations of workers' basic rights. In addition, physical and psychological pressure and the lack of legal protection seen from the lack of clarity in labor regulations in the entertainment sector contribute to the occurrence of exploitative practices, further aggravating these conditions. This article contributes to a critical study of working conditions in the cultural industry and encourages the need for a more comprehensive labor protection policy. This article also underlines the importance of building public awareness of the hidden realities behind the entertainment world and urges readers to take a more critical look at popular entertainment phenomena and demand structural improvements in the protection of labor rights and structural reforms in the management of the circus entertainment industry to create a fair and humane working environment.